Democratic transition and sectarian populism: the case of Lebanon - Salamey, Imad (2015)
Despite being considered as one of the oldest constitutional democracies in the Middle East, Lebanon has been confronted with periodical institutional crises and civil violence. A protracted transitional period towards democracy has threatened the autonomy of deeply fragmented sectarian groups, and has instigated a polarizing struggle over nationhood. Fearing the degradation of their power to a majoritarian order, sectarian leaders have resorted to various mobilization strategies to obstruct the emergence of a unifying national identity and democratic state. Consequently, a chronically weak state has emerged, divided along antagonistic sectarian loyalties with power shared according to sectarian consociationalism. In order to reveal the tenets of sectarian populism in Lebanon and their impacts on nation-building, the state and democratic transition, a nationwide opinion survey was conducted by the Lebanese American University (LAU), Beirut, during January of 2011 with a random sample of 586 Lebanese respondents divided along sectarian affiliation. The survey examined differential populist mobilization among major sectarian groups and revealed potential explanatory variables. The results shed light on the formation of populism in a divided society and the challenges it poses for democratic transitions in Lebanon and perhaps in transitional Middle Eastern states.